Paris Fashion and World War Two global diffusion and Nazi control - McLoughlin, Marie; Taylor, Lou (Bloomsbury Publishing, 2020)
"In 1939, fashion became an economic and symbolic sphere of great importance in France. Invasive textile legislation, rationing and threats from German and American couturiers were pushing the design and trade of Parisian style to its limits. It is widely accepted that French fashion was severely curtailed as a result, isolated from former foreign clients and deposed of its crown as global queen of fashion. This pioneering book offers a different story. Arguing that Paris retained its hold on the international haute couture industry right throughout WWII, eminent dress historians and curators come together to show that, amid political, economic and cultural traumas, Paris fashion remained very much alive under the Nazi occupation - and on an international level"--
Online-Ausgabe erschienen bei Bloomsbury Fashion Central: 2021
Keywords: Fashion & society; Clothing and dress -- France -- Paris -- History -- 20th century; Fashion -- France -- Paris -- History -- 20th century; Women's clothing -- France -- Paris -- History -- 20th century; World War, 1939-1945 -- Social aspects -- France; Kontrolle; Bekleidungsindustrie; Mode; Zweiter Weltkrieg; Textilindustrie; Nationalsozialismus; Paris; Frankreich; Aufsatzsammlung